Heidegger, nazismul și stânga franceză - Paul Kun (Polis: Revista de Stiinte Politice, 2020)
This essay proposes to examine the relationship between philosophical thought and political action in the XX Century, especially the Heidegger Case and the mystery of the unexpected popularity of this German philosopher among left radical intellectuals from France, after the second world war, despite de fact that Heidegger was a member of Nazi party from 1933 and was very active politically between 1933 and 1934. Heidegger was attracted by Nazism because he shared some common political ideas with it. Butcan we tell the same about the young leftist French intellectuals? I think we can respond affirmativelyto this question and I present the common political ideas which explain this attraction.